Cenzura prasy partyjnej na przykładzie „Gazety Pomorskiej” z lat 1949–1950 - Ciszewska-Pawłowska, Wanda (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Gazeta Pomorska, the press organ of the Provincial Committee of the Polish United Workers' Party in Bydgoszcz, is an example of the party’s press closely related to a political grouping. The journal was created in 1949 as a result of merging local Pomeranian magazines: "Głos Pomorza” from Toruń and "Gazeta Zachodnia” from Bydgoszcz. The subject of the new periodical referred to the nature of the previous magazines. The novelty was the close connection with party issues. Censorship assessments of "Gazeta Pomorska" prepared by the Provincial Office of Control of Press, Publications and Shows (WUKPPiW) in Bydgoszcz in 1949 are not as enthusiastic as they would expect for a periodical related to the party in power. Their character and tone depend, among others, on the guidelines presented at the meetings of the party’s press editors, organized by the Press and Publishing Department of the Central Committee of the Polish United Workers' Party (Wydział Prasy i Wydawnictw KC PZPR).